Development and validation of a TaqMan Array for cancer mutation analysis. Issue 1 (February 2016) - Kikuchi, Hugh; Reiman, Anne; Nyoni, Jenifer; Lloyd, Katherine; Savage, Richard; Wotherspoon, Tina; Berry, Lisa; Snead, David; Cree, Ian A.
Abstract: Introduction: Optimal cancer treatment with targeted agents requires rapid, comprehensive and accurate molecular assays to analyse actionable oncogenic mutations across multiple tumour types. Materials and Methods: We describe a PCR panel based on the 384 well TaqMan Array® (Thermo Fisher Scientific). This allows measurement of common RAS (NRAS and KRAS), EGFR and BRAF mutations in a single assay (the REB Array), analysing 44 mutations in 7 samples per plate. This retrospective study includes 96 patients with NSCLC (n = 42), colorectal cancer (n = 26), and melanoma (n = 28) with previous mutational analysis. Samples with discrepant results were sequenced to confirm the result. Results: The REB achieved 93% concordance with the Therascreen EGFR assay (Qiagen), 95% concordance with the KRAS castPCR assay (Thermo Fisher), and 100% concordance with the cobas BRAF assay (Roche). There were 2 true discrepancies, most likely a result of sample quality or differences in sensitivity between the assays that depend on set thresholds to determine the presence of mutations. Analysis of the performance of the REB Array gave an overall sensitivity of 92%, with a positive predictive value of 100% and negative predictive value of 84.24%. Conclusion: The REB array is comparable to competing PCR methods with the additional advantages of a broader range of mutations, simplified manual handling, and reduced overall cost per sample.